A case of psoriasiform drug eruption caused by temozolomide. Issue 5 (27th July 2022) - Oguro, Tokuko; Nakajima, Kimiko; Aoki, Natsuko; Yamamoto, Mayuko; Sano, Shigetoshi
Abstract: Psoriasiform drug eruption is defined as condition similar to psoriasis triggered by drug administration, including de novo development of psoriasis or exacerbation of pre‐existing psoriasis. Herein, we describe a 52‐year‐old Japanese woman, who developed disseminated psoriasiform lesions following administration of temozolomide, a remedy for glioblastoma, although cutaneous adverse events by this drug was very rare. In addition, we assume that altered inflammatory signals associated with psoriasis, such as activation of signal transducer and activator of transcription 3 (STAT3), might be involved in the underlying pathomechanism of drug eruption caused by temozolomide. Abstract : Psoriasiform drug eruption is defined as condition similar to psoriasis triggered by drug administration, including de novo development of psoriasis or exacerbation of pre‐existing psoriasis. We report a case who developed psoriasiform lesions following administration of temozolomide, a remedy for glioblastoma, although cutaneous adverse events by this drug was very rare.